Understanding and Addressing Determinants of Condom Use Compliance Among Clients of Sex Workers: A Public Health Perspective - Arwan (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2024)
Condom use compliance among clients of sex workers is a critical factor in preventing sexually transmitted infections (STIs) and ensuring public health safety. This study systematically reviews global research on the determinants of condom use compliance, focusing on socio-economic, legal, and behavioral influences. A comprehensive literature search was conducted using PubMed, Scopus, and Google Scholar, incorporating studies published within the last 15 years. Findings indicate substantial regional disparities in condom use, with compliance rates significantly lower in areas where sex work is criminalized and financial negotiations frequently lead to unsafe practices. Additionally, substance use and perceived trust in repeat client relationships contribute to decreased condom adherence. The discussion highlights systemic barriers, including stigma and law enforcement practices, which deter sex workers from advocating for safer sex practices. Effective strategies to enhance compliance include legal decriminalization, economic support programs, and community-driven interventions. These approaches empower sex workers to negotiate safer practices while mitigating risks associated with STI transmission. Future research should focus on evaluating policy reforms, assessing long-term behavioral shifts, and refining targeted interventions for different client demographics. Addressing structural and behavioral challenges through comprehensive public health policies is imperative for reducing infection rates and improving sexual health outcomes.